Bidayatul Hidayah Book for Elementary Children in the 21st Century: Character Value Education - Yudhi Septian Harahap; Nur Khafifah Indriyani; Saripah Aini; Ira Suryani (Universitas Pahlawan Tuanku Tambusai, 2023)
For humans, character plays a crucial part in preventing them from leaving their sphere and entering that of servants. The purpose of this study is to examine how character values are taught in elementary school-aged children's Bidayah Hidayah novels in the twenty-first century. A descriptive qualitative research approach is used in this study. The data and material used in this study come from research publications written by prior analysts and combine two sources, namely particular vital information and optional information. A way of gathering data for this study's data collecting was library research. Two things come out of this study's findings: first, individual character; and second, social character. Whereas Imam Al-unique Ghazali's personality links it to adab to Allah. In the meantime, Imam Al-social Ghazali's nature connects it to adab for teachers. Additionally, consider the effects on elementary-aged kids in the twenty-first century. Promiscuity that deviates from the norm will harm society, psychology, and the body as well as undermine morals and have a detrimental effect on future generations. As a result, through the Bidayatul Hidayah book, wisdom is attained since parents and educators can impart the value of religious education as a tool for developing into a perfect human being while also teaching children manners to Allah SWT and to educators.